Factor out the greatest common factor from each polynomial.

(5r-6)(r+3)-(2r-1)(r+3)

(5r-6)(r+3)-(2r-1)(r+3)

1 Answers

Best Answer

Step 1

Given

(5r-6)(r+3)-(2r-1)(r+3)

Step 2

Factor out the greatest common factor;

(5r-6)(r+3)-(2r-1)(r+3)=(r+3){(5r-6)-(2r-1)}

=(r+3){5r-6-2r+1}

=(r+3)(3r-5)

Factors are; (r+3)(3r-5)

Given

(5r-6)(r+3)-(2r-1)(r+3)

Step 2

Factor out the greatest common factor;

(5r-6)(r+3)-(2r-1)(r+3)=(r+3){(5r-6)-(2r-1)}

=(r+3){5r-6-2r+1}

=(r+3)(3r-5)

Factors are; (r+3)(3r-5)